The development of Geography as a university subject in Dundee. - Turner, W. H. K. (Scottish Geographical Journal)
In the mid-1980s W.H.K. (Keith) Turner drafted a short history of the emergence of Geography as an academic subject taught and researched at what is now the University of Dundee. The unpublished mimeograph containing this history was drawn upon in one published account of Geography at Dundee [Findlay & Werritty, 2010. Putting geography in its place. Scottish Geographical Journal, 126(4), 215–230], but remained itself unpublished. Prompted by a chance rediscovery of this mimeograph more recently, there is warrant for now making Turner's account more widely available as part of the present journal's 'Making Scottish Geography' series. Attempting to keep something of the original typescript appearance of this account, it is reproduced here alongside a foreword that briefly outlines something of its content, as well as drawing out certain threads for further consideration.